Intervención optométrica en paciente femenino de 22 años con insuficiencia acomodativa que asiste a la Óptica Mundo Visión de la ciudad de Quevedo. - Rojas Intriago, Carla Noelia (2025)
This clinical case describes the optometric intervention in a 22-year-old female patient with accommodative insufficiency, characterized by blurred vision, eye fatigue, and headaches during near vision activities. The patient, a forestry engineering student, had no history of wearing lenses or previous optometric examinations. A vision therapy plan was implemented for 12 weeks, focused on improving his accommodative capacity and reducing symptoms. The results showed a notable decrease in headaches, improvement in concentration during close tasks, and disappearance of episodes of double vision and blurriness. Vision therapy proved to be effective, avoiding the need for optical corrections and improving the patient's quality of life. This case supports vision therapy as a non-invasive and effective alternative for the management of accommodative insufficiency in young adults.